2020
DOI: 10.1096/fasebj.2020.34.s1.05510
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic fasting mitigates metabolic and cardiovascular dysfunction in a prediabetic rat model: Possible role of adipose inflammation

Abstract: The risk of cardiovascular complications in type 2 diabetes increases as early as in the prediabetic stage. Our previous studies showed that perivascular adipose tissue inflammation contributes to vascular and cardiac autonomic dysfunction in prediabetic rats. Intermittent fasting has been extensively studied in the management of metabolic diseases. Here, we aim to examine the impact of therapeutic fasting (TF) on the metabolic and cardiovascular stress among prediabetic rats. Male SD rats (4–5weeks) were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Interestingly, the change in fat pad size was found to be triggered by IF alone, regardless of the daily caloric intake, and independent of the change in body weight as animal studies showed a decrease in size and weight of adipose depots, with mild or no change in total body weight (Varady et al, 2007;Varady et al, 2009;Varady et al, 2010;Liu et al, 2019b). Certainly in our work, a calorie restricted regimen of a HFD failed to exert any corrective effect on CAN and PVAT inflammation involvement in rats (Al-Assi et al, 2018) as opposed to isocaloric IF (12-h feeding/12-h fasting) (Dwaib et al, 2020). In studies involving obese human subjects, IF appeared to reduce total fat mass with varying fasting protocols such as intermittent continuous energy restriction for 2 days a week and alternate day fasting (Harvie et al, 2011;Bhutani et al, 2013;Tinsley and La Bounty, 2015), and circulating markers of inflammation (Harvie et al, 2011;Wang et al, 2020), the latter effect being more marked in obese than in normal weight subjects (Wang et al, 2020).…”
Section: Adipose Tissue Remodeling In Response To Therapeutic or Intermittent Fastingmentioning
confidence: 45%
See 1 more Smart Citation
“…Interestingly, the change in fat pad size was found to be triggered by IF alone, regardless of the daily caloric intake, and independent of the change in body weight as animal studies showed a decrease in size and weight of adipose depots, with mild or no change in total body weight (Varady et al, 2007;Varady et al, 2009;Varady et al, 2010;Liu et al, 2019b). Certainly in our work, a calorie restricted regimen of a HFD failed to exert any corrective effect on CAN and PVAT inflammation involvement in rats (Al-Assi et al, 2018) as opposed to isocaloric IF (12-h feeding/12-h fasting) (Dwaib et al, 2020). In studies involving obese human subjects, IF appeared to reduce total fat mass with varying fasting protocols such as intermittent continuous energy restriction for 2 days a week and alternate day fasting (Harvie et al, 2011;Bhutani et al, 2013;Tinsley and La Bounty, 2015), and circulating markers of inflammation (Harvie et al, 2011;Wang et al, 2020), the latter effect being more marked in obese than in normal weight subjects (Wang et al, 2020).…”
Section: Adipose Tissue Remodeling In Response To Therapeutic or Intermittent Fastingmentioning
confidence: 45%
“…Another study on a rat model found that both 40% calorie restriction and alternate day fasting reduced the low frequency component in the diastolic blood pressure variability, a marker of reduced sympathetic activity, and increased high frequency component in heart rate variability, which is reflective of the parasympathetic tone, both being indicative of positive modulation of cardiovascular state (Mager et al, 2006). Specifically, in the context of early metabolic dysfunction, preliminary data indicate that not only did IF (12-h feeding/12-h fasting) improve parasympathetic cardiac autonomic neuropathy, this was also associated with amelioration of PVAT inflammation in an HFD-fed rat model of metabolic dysfunction (Dwaib et al, 2020).…”
Section: Cardiometabolic Syndrome and Therapeutic Or Intermittent Fastingmentioning
confidence: 93%
“…Calorie intake was determined for each rat based on the amount of food consumed daily. Anesthetized rats were sacrificed by decapitation after 12 (age = 17 weeks) or 24 weeks (age = 29 weeks) of feeding (Dwaib et al, 2020).…”
Section: Experimental Designmentioning
confidence: 99%
“…While the search for such tools is ongoing, simple interventions leading to this outcome might include modification of caloric intake. Indeed, previous research showed that approaches involving caloric restriction and intermittent fasting were associated with an ameliorative effect on both perivascular adipose inflammation and CAN [99,136].…”
Section: Therapeutic Interventions To Ameliorate Can In T2dmentioning
confidence: 99%